2013
DOI: 10.1158/0008-5472.can-12-2796
|View full text |Cite
|
Sign up to set email alerts
|

Acidity Generated by the Tumor Microenvironment Drives Local Invasion

Abstract: The pH of solid tumors is acidic due to increased fermentative metabolism and poor perfusion. It has been hypothesized that acid pH promotes local invasive growth and metastasis. The hypothesis that acid mediates invasion proposes that H+ diffuses from the proximal tumor microenvironment into adjacent normal tissues where it causes tissue remodeling that permits local invasion. In the current work, tumor invasion and peritumoral pH were monitored over time using intravital microscopy. In every case, the peritu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
924
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,124 publications
(956 citation statements)
references
References 38 publications
26
924
0
6
Order By: Relevance
“…Unlike interventions that alter intracellular pH by targeting one (or more) of many membrane-bound transporter proteins, extracellular pH could be manipulated by altering H þ diffusivity or buffering capacity. Raising mobile buffering capacity with systemic bicarbonate offers an attractive means of changing the course of acid-driven somatic evolution by ablating the underlying selection pressure [88]. The steady flow of new data in support for the prominent role played by H þ ions in cancer will keep pH in the spotlight for novel therapeutic approaches for years to come.…”
Section: Ph Sensing Ph-driven Selection and Clinical Perspectivesmentioning
confidence: 99%
“…Unlike interventions that alter intracellular pH by targeting one (or more) of many membrane-bound transporter proteins, extracellular pH could be manipulated by altering H þ diffusivity or buffering capacity. Raising mobile buffering capacity with systemic bicarbonate offers an attractive means of changing the course of acid-driven somatic evolution by ablating the underlying selection pressure [88]. The steady flow of new data in support for the prominent role played by H þ ions in cancer will keep pH in the spotlight for novel therapeutic approaches for years to come.…”
Section: Ph Sensing Ph-driven Selection and Clinical Perspectivesmentioning
confidence: 99%
“…8 Using dorsal window chambers, we have demonstrated that acidic environments promote tumor invasion and growth by degrading adjacent extracellular matrix]. 9,10 Thus, we view the intratumoral environment as "niche engineering" wherein cancer cells, in response to Darwinian dynamics, generate an environment that promotes their own growth and invasion 11 at the expense of the stromal cells into which they invade. Acidosis also inhibits anti-tumor immunity and promotes immune editing.…”
Section: Introductionmentioning
confidence: 99%
“…It is anticipated that the slightly acidic microenvironment of the tumor would lead to accelerated cleavage of PTX from the conjugate backbone compared with the non-tumor area [32,33]. Therefore, the hydrolysis of PEG-PTX could possibly take place prior to the internalization of the conjugates, which possibly resulted in a high proportion of PTX in the interstitial tumor area within the lungs.…”
Section: Discussionmentioning
confidence: 99%